ANALYSIS OF PROBLEM SOLVING SKILLS OF X GRADE STUDENTS FOR TRIGONOMETRY MATERIAL AFTER EXPERIENCING LEARNING USING A REALISTIC MATHEMATICS APPROACH ASSISTED BY GEOGEBRA - Malau, Evi Ervera; Julie, Hongki (Jurnal Pendidikan Matematika (JUPITEK), 2024)
One of the abilities that students need to build when learning mathematics is problem solving ability, so that students can implement their mathematical knowledge. From the results of student tests in the previous year and exploring the problem, researchers found that the problem solving ability of students faced for Trigonometry material is analyzing problems, organizing ideas and solving problems. The purpose of this study is to describe how students' problem solving skills after experiencing learning with the Realistic Mathematics Education Approach (PMR) for Trigonometric Comparison material assisted by Geogebra. The research subjects were 31 grade X students in one of the private high schools in Bekasi city in 2024/2025. The data collection methods used were field notes, written tests, and interviews. The instrument validation technique used expert validation techniques, while to validate the data, triangulation techniques were used. The research results from the written test are as follows: (a) the most difficulties found for problems 1 and 2 were executing the plan to get a solution, and looking back at the solution process; (b) the most difficulties found for problem 3 were making a plan, executing the plan, and looking back at the solution process. From the interviews with five students, it was found that the most experienced difficulties were making a plan, carrying out the plan, and reviewing the solution process; (b) the most experienced difficulties for problem 3 were making a plan, carrying out the plan, and reviewing the solution process